Identification of promising nutraceuticals against filarial immune-modulatory proteins: insights from in silico and ex vivo studies. Issue 35 (11th August 2022) - Kumar, Vipin; Mishra, Ayushi; Singh, Anchal
Abstract : Here in drug docking analysis, molecular dynamics simulations and ex vivo approaches were used to demonstrate the anti-filarial effects of nutraceuticals against immune modulatory proteins of lymphatic filarial parasites. Abstract : Lymphatic filariasis is a neglected tropical disease affecting over 863 million people in 47 countries of the world. The anti-filarial drugs, diethylcarbamazine, albendazole, and ivermectin, are effective only at the larval stages and have proven completely ineffective as adulticides. Besides this, a long-term use of these drugs is associated with several side effects including drug toxicity. Nutraceuticals have emerged as better alternatives for long term treatments due to their safety and lesser side effects. In the present work, we have used drug docking analysis and molecular dynamics simulation approaches to explore the effect of anti-inflammatory nutraceuticals against the immune-modulatory proteins of filarial worms. The filarial proteins enolase, ES-62 precursor, serpin, and cystatin, which are highly efficient in host immune modulation were targeted with more than 50 nutraceuticals. In the in silico study nutraceuticals such as naringin, β-carotene, and emodin showed higher binding efficacy and lower dissociation constant as compared to anti-filarial drugs. Molecular dynamics simulation results showed that immune-modulatory proteins formed highly stable complexes with naringin, β-carotene, and emodin over the entire MD simulation run. The nutraceutical emodin formed the most stable system in silico and hence its effect was investigated on adult filarial parasites under ex vivo conditions too. Emodin significantly affected the motility, viability, ROS production, and genomic DNA fragmentation of filarial parasites. Further in vivo and in vitro studies will help in understanding the mechanism of action of emodin at the molecular level and would help in the development of more effective anti-filarial drugs.